2020
DOI: 10.1111/iwj.13478
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of beta antagonist in burned patients: A systematic review and meta‐analysis

Abstract: Beta antagonist is one of the most effective and the least toxic pharmacological treatments to attenuate the raised catecholamine effects for burned patients. To evaluate the effectiveness and safety of beta blocker compared with placebo or usual care in burned patients, a meta‐analysis of randomised controlled trials (RCTs) was conducted. We searched the database of PubMed, Embase, the Cochrane Library, and Web of Science to 10 April 2020. Two investigators independently assessed articles for inclusion and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Two systematic reviews on RCTs in burn patients have recently been published. These reviews also included studies of burn patients under the age of 18 [ 60 , 61 ]. In these systematic reviews there was no significant differences in mortality between the β -blocker and the control groups, but in the individual trials propranolol seemed to improve wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews on RCTs in burn patients have recently been published. These reviews also included studies of burn patients under the age of 18 [ 60 , 61 ]. In these systematic reviews there was no significant differences in mortality between the β -blocker and the control groups, but in the individual trials propranolol seemed to improve wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Stormer et al (2019) also showed that antihypertensive drugs improve wound healing to some extent (34), which was in line with the results of this study. The administration of propranolol improves wound contraction and causes proper repair of some superficial parts at the border of the deep burn area, thus improving the healing process and reducing graft preparation time (35,36). Avoiding wound infection, reducing catabolism, and maintaining pro-…”
Section: Discussionmentioning
confidence: 99%
“…A study by MA J et al showed that the use of beta antagonists in burn patients reduces the length of stay in the hospital in adults, shortens the preparation time for transplantation and reduces the burden on the heart, without increasing mortality, and reduces sepsis and PTSD compared to people who received usual care. Therefore, beta antagonist can be considered as a suitable treatment strategy in burn patients (35).…”
Section: Frontiers In Emergency Medicine In Pressmentioning
confidence: 99%
See 1 more Smart Citation